Intervention Approach to the Menopausal Women in Rural Bangladesh - Yasmin, Nahid; Sultana, Sayeeda; Habib, Shahin Akhter Jahan; Khatun, Khodeza (Bangladesh Medical Journal, 2009)
To compare the level of knowledge about menopause in terms of its cause, problems and care seeking pattern among the rural women after a health education intervention program. It was a cross sectional intervention type study. In the study, the outcome of intervention was obtained by comparing pre intervention and post intervention of same study population to test if there is any difference in knowledge level. The total intervention program was evaluated ranking their answers and found that before the intervention the only 27.8% respondents had some knowledge regarding menopause related problems and 72.2% had no such perception. After intervention it was observed that 49.27% respondents improved their knowledge, statistically it was found significant. The study was conducted to assess and compare the improvement of knowledge of rural women regarding menopause through educational interventions program. From the study findings, it revealed the significant achievement among the respondents regarding the knowledge on menopause, health care seeking behaviour through an educational intervention program imparted to them. The aim of intervention program is that there should be some degree of changes about knowledge, attitude and behaviour. From the intervention program knowledge of the rural women upgraded. Though this study may not necessarily reflect the actual picture. Through the study the intervention program was found very effective which might be replicate in the country through a national program. Key word: Knowledge on menopausal problems, Health care seeking pattern. DOI: 10.3329/bmj.v38i1.3580 Bangladesh Medical Journal 38(1) 2009 9-14